A Delphi study analysis of ICT skills in secondary vocational schools - Mohamad Yassin, Ruhizan; Minghat, Asnul Dahar; Rahman, Saemah; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
The development of a high-quality education system is one of Malaysia's main priorities. Focus has centred on the development of experienced, competent, progressive human capital bearing high moral and ethical standards. The Education Development Master Plan (EDMP) 2006-2010 submitted by the Ministry of Education implements 22 vocational subjects (VS) in secondary schools. This is to develop vocational skills in preparing students to meet the need for skilled and semi-skilled workers after graduating high school to support economic development. This study identifies the elements of sustainability for the implementation of VS in secondary schools in Malaysia based on the strategy outlined by the International Centre for Technical and Vocational Education and Training (UNEVQC) based in Bonn, Germany. The methodology used for this study is the Delphi study. Twelve panels of experts in the field of technical and vocational education in Malaysia were involved in the study consisting of four rounds of Delphi. In the first round, interviews were conducted on a panel of experts on the basis of interview protocols. The results of these interviews showed that ICT skills are one of the elements necessary for the preservation of VS teaching in secondary schools. Subsequently a questionnaire was developed with the aid of an expert panel in the second to fourth rounds of the Delphi study. The questionnaires developed will be used by VS teachers in order to gain a perception of ICT skills in the conservation of VS teaching in secondary schools.